Developing Complex, Mass-Customized Products in SME Networks: Perspectives From Co-Creation, Solution Space Development, and Information System Design - Grafmüller, Leontin K.; Hankammer, Stephan; Hönigsberg, Sarah; Wache, Hendrik (International Journal of Industrial Engineering and Management, 2018)
Already for nearly three decades, Mass Customization (MC) has been described as a viable business model for companies in diverse sectors. Nonetheless, the introduction and the successful operation of an MCapproachis a challenging endeavor for companies of all sizes. In this article,special attention is givento small and medium-sized enterprises (SMEs), which increasinglycollaborate in networks to successfully develop complex, mass-customized products. Whilecollaboration allows for pooling several areas of expertise,the cross-organizational development poses challenges in manifold regards. To study these challenges, we set up a network business process model developed with four SMEs from the German high-tech textile industry. Based on the current literature on capabilities for MC, we evaluate the challenges of MC in SME networks detected in our network business processmodel to underpin the need for further research.In our study, we detail the conceptualanalysisof such network-based scenarios along our process model for three focal areas: (1) co-creation, (2) solution space development, and (3) information systemdesign. We construe the need for further research and derive implications for both academia and practice. Article history: Received (03.10.2018); Revised (27.11.2018); Accepted (05.12.2018)